Study on dynamic mechanical properties of magnetorheological elastomers based on natural rubber/thermoplastic elastomer hybrid matrix. (12th September 2018) - Song, Xincheng; Wang, Wenju; Yang, Fufeng; Wang, Guoping; Rui, Xiaoting
Abstract: Magnetorheological elastomers (MREs) are a kind of smart materials which is mainly made up of matrix materials and magnetic particles. Its mechanical properties can be controlled under external magnetic field. In this study, the MREs based on natural rubber and a blend of natural rubber mixed with thermoplastic elastomer styrene (ethylene butylene) styrene (SEBS) were prepared respectively. The sample of MREs were prepared using conventional rubber-mixing technology. The changes of dynamic rheological properties, mechanical properties, and thermal stability were tested. The results showed that the MREs based on natural rubber/thermoplastic elastomer SEBS had better processability, higher zero modulus and MR effect than MREs based on natural rubber. The zero modulus and MR effect of MREs were increased after adding thermoplastic elastomer to natural rubber matrix. The thermal stability of MREs based on natural rubber/thermoplastic elastomer SEBS had no difference with MREs based on pure natural rubber. An internal structure that the sulphur connect the SEBS with natural rubber was proposed to describe the thermal stability of MREs based on natural rubber/thermoplastic elastomer SEBS.